ACCOUNTING TREATMENT OF STOCK VALUATION DIFFERENCES IN FINANCIAL MARKETS - Tahseen Abdulhasan Lafta (Scholar Express Journals, 2025)
Stocks are one of the main financial instruments traded in the financial markets, as they represent an investment vehicle for investors and sources of financing for companies
Keywords: accounting processing; Valuation; stocks; financial markets